2018
DOI: 10.1111/os.12369
|View full text |Cite
|
Sign up to set email alerts
|

Role of Teriparatide in Glucocorticoid‐induced Osteoporosis through Regulating Cellular Reactive Oxygen Species

Abstract: Teriparatide can reduce the cellular ROS level caused by glucocorticoids to facilitate the proliferation of osteocytes through activating the AKT pathway. Meanwhile, the activated AKT can inhibit the activity of proteolytic enzyme caspase-3 and prevent the activation of apoptosis cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Hodsman et al [54] stated that terparatide inhibit bone resorption by diminishing the number, function, and life span of osteoclasts. Wang et al [9] confirmed that teriparatide can diminish the level of the cellular ROS and stimulate osteocytes growth via triggering the protein kinase B (PKB) pathway. Meantime, the activated PKB can suppress caspase-3 proteolytic enzyme and stop the activation of apoptosis cascade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hodsman et al [54] stated that terparatide inhibit bone resorption by diminishing the number, function, and life span of osteoclasts. Wang et al [9] confirmed that teriparatide can diminish the level of the cellular ROS and stimulate osteocytes growth via triggering the protein kinase B (PKB) pathway. Meantime, the activated PKB can suppress caspase-3 proteolytic enzyme and stop the activation of apoptosis cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Teriparatide enhances bone formation and subsequently bone resorption. It increase cortical bone thickness as well as trabecular bearing and interlink [9] . Wang et al [9] explained that teriparatide can diminish the level of the cellular ROS and stimulate osteocytes growth via triggering the protein kinase B (PKB) pathway Meantime, the activated PKB can suppress caspase-3 proteolytic enzyme and stop the activation of apoptosis cascade.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous reports have shown that estrogen deficiency, a lack of exercise, and oxidative stress play a central role in the onset and development of postmenopausal osteoporosis 3,4 . Oxidative stress can produce excessive reactive oxygen species (ROS) and promote osteoblast damage [5][6][7] . Furthermore, ROS accelerates the apoptosis of osteoblasts, inhibiting their differentiation and impairing bone formation 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Next to neutrophils, an inhibition of intracellular ROS production after prednisolone and dexamethasone administration is also described for platelets [ 101 ]. However, in osteocyte-like cells, dexamethasone increased the ROS level compared to control groups [ 102 ]. These results underline the findings of the present study as prednisolone seemed to support pathogen killing, NET release and ROS production in certain dosages.…”
Section: Resultsmentioning
confidence: 99%